Paediatric intentional head injuries in the emergency department: A multicentre prospective cohort study. (26th November 2018) - Babl, Franz E; Pfeiffer, Helena; Dalziel, Stuart R; Oakley, Ed; Anderson, Vicki; Borland, Meredith L; Phillips, Natalie; Kochar, Amit; Dalton, Sarah; Cheek, John A; Gilhotra, Yuri; Furyk, Jeremy; et al.
Abstract: Objective: Although there is a large body of research on head injury (HI) inflicted by caregivers in young children, little is known about intentional HI in older children and inflicted HI by perpetrators other than carers. Therefore, we set out to describe epidemiology, demographics and severity of intentional HIs in childhood. Methods: A planned secondary analysis of a prospective multicentre cohort study was conducted in 10 EDs in Australia and New Zealand, including children aged <18 years with HIs. Epidemiology codes were used to prospectively code the injuries. Demographic and clinical information including the rate of clinically important traumatic brain injury (ciTBI: HI leading to death, neurosurgery, intubation >1 day or admission ≥2 days with abnormal computed tomography [CT]) was descriptively analysed. Results: Intentional injuries were identified in 372 of 20 137 (1.8%) head‐injured children. Injuries were caused by caregivers (103, 27.7%), by peers (97, 26.1%), by siblings (47, 12.6%), by strangers (35, 9.4%), by persons with unknown relation to the patient (21, 5.6%), other intentional injuries (8, 2.2%) or undetermined intent (61, 16.4%). About 75.7% of victims of assault by caregivers were <2 years, whereas in other categories, only 4.9% were <2 years. Overall, 66.9% of victims were male. Rates of CT performance and abnormal CT varied: assault by caregivers 68.9%/47.6%, by peers 18.6%/27.8%, by strangers 37.1%/5.7%. ciTBI rate was 22.3% in assault by caregivers, 3.1% when caused by peers and 0.0% with other perpetrators. Conclusions: Intentional HI is infrequent in children. The most frequently identified perpetrators are caregivers and peers. Caregiver injuries are particularly severe.